Theory of the Personality’s Spiritual Self-Development - Kolisnyk, Oleksiy P. (Psychological Prospects Journal, 2017)
Spiritual self-development of the personality is progressing due to disidentification with leading contemporary meanings hierarchy of meanings and the degree of identification with fundamentally new leading meanings of the next major stage of development. The shift of the leading meanings of the hierarchy of meanings of the individual to radically new meanings loose from the previous semantic field and activates the hidden resources of the new semantic field. Key words: postnonclassical science, western and eastern paradigm, personality, identity, spirituality, self-development, value, meaning, hierarchy of meanings, world view, self-concept , the stream of psyche, level of development , meaning field, fundamentally new purpose, willpower effort, mental mechanism of self-development, identification disidentification, shift of a meaning on the purpose, theory of personality, psychotherapy, spiritual practices, altered states of mind, peak experiences, spontaneity.